Association between Knowledge level of Respondents about Coriander Production Technology - Meena, D K; Bareth, L S; Badhala, B. S. (Indian Journal of Extension Education, 2012)
The present study was conducted in purposively selected Khanpur Panchayat Samiti of Jhalawar district, to study association between knowledge level of respondents about coriander (Coriandrum sativum L.). From Khanpur Panchayat Samiti, five Gram Panchayats, 32 growers (16 tribal and 16 non-tribal) were selected on the basis of having highest area and production of coriander among all the Gram Panchayats of Samiti. In each village seed spices are not only cash-crop but also they can be termed as dynamic crop commodities particularly in the view of their great export potential. There was significant association between different variables, viz. age, education, family size, family type and size of land holding with knowledge level of tribal, non-tribal as well as over all coriander growing farmers.
Keywords: Association; Knowledge coriander; Tribal and non-tribal farmers